Pengaruh Etika Profesi, Pengalaman, dan Profesionalisme Terhadap Kualitas Audit Di KAP Kota Batam - Fanny Rahma Sari; Vargo Christian L. Tobing (SCIENTIA JOURNAL, 2026)
This research is conducted to analyze the extent to which professional ethics, work experience, and professionalism influence audit quality at Public Accounting Firms (KAP) located in Batam. The study adopts a quantitative research approach with a survey-based design to obtain empirical evidence from practitioners directly involved in audit activities. The population of this study consists of all active auditors working in six Public Accounting Firms registered with the Indonesian Institute of Public Accountants (IAPI) in 2025, including partners, managers, senior auditors, and junior auditors, totaling 30 respondents. A saturated sampling technique is employed, meaning the entire population is used as the research sample to ensure comprehensive representation. Primary data are collected through structured questionnaires distributed via Google Forms, measured using a Likert scale. Prior to analysis, the research instruments undergo validity and reliability testing to ensure data accuracy and consistency. Data analysis is carried out using SPSS version 26, incorporating descriptive statistical analysis, classical assumption tests such as normality, multicollinearity, and heteroscedasticity and multiple linear regression analysis. Hypothesis testing is performed through t-tests, F-tests, and the calculation of the coefficient of determination (R²). The findings reveal that professional ethics and experience do not have a significant effect on audit quality, whereas professionalism shows a significant positive influence. These results suggest the importance of strengthening professional attitudes and competencies through continuous training and standardized procedures. This study contributes theoretically to audit quality literature and provides practical insights for regulators, professional bodies, and KAP management in improving audit practices.